Merit, Discrimination, and Democratization : An Analysis of Promotion Patterns in Indonesia's Civil Service - World Bank (World Bank, Washington, DC, 2019)
What effect does democratization have on meritocratic practices in the civil service? Democratization increases performance incentives within the bureaucracy. This leads to more meritocracy for individuals with performance-enhancing characteristics, such as educational attainment, which cross-cut political cleavages. When politicized cleavages align with civil servants' performance-enhancing characteristics, democratization increases discrimination. The author test this argument using administrative data from Indonesia that covers the full universe of career histories of all 4 plus million currently active civil servants. The author exploits the exogenous timing of Indonesia's democratization in 1999, paired with an individual-level panel data design, for identification purposes. The author finds strong evidence that democratization amplified the positive effects of educational attainment on career advancement but simultaneously worsened the career prospects of female and religious minority civil servants. We replicate these patterns for the staggered introduction of direct elections at the district government level. The gender and religious minority penalties are strongest for promotions at the lowest levels of the administrative hierarchy and for employees of departments under the leadership of conservative Muslim parties. Increased female leadership in the bureaucracy does not alleviate these penalties.